Kajian Hubungan Nilai Willingness To Accept (Wta) Terhadap Harga Pasir Yang Terinternalisasi Biaya Eksternalitas Dengan Tingkat Pengeluaran Dan Pendapatan Masyarakat Di Kabupaten Merauke - Maria Maghdalena Diana Widiastuti; Norce Mote (Akuatik: Jurnal Sumberdaya Perairan, 2019)
Study of The willingness to accept (WTA) is one approach to assess environmental services. The WTA estimates how much people want to be paid to prevent environmental damage (willingness of producers to receive compensation) with the deterioration of environmental quality. Coastal sand mining in Nasai Beach has caused coastal damage, damaged mangrove ecosystems, reduced fisheries production, and caused damage to roads. One effort to overcome this externality through the determination of sand price that internalized the externality cost. The proposed of sand price is IDR 391,924.00 /m3. This study aims (1). Analyzing the willingness to accept ofsand price with internalized the externality cost from consumers of sand, sand agents and sand sellers, (2). Analyzing the level of income and expenditure of the community, (3). Assessing the correlation of WTA values ​​with the level of expenditure and income of respondents. The methodology used mean WTA, Pearson correlation test and cross tabulation. The results showed that 72.3% of respondents were willing to accept the price of sand which internalized the externalities cost. The amount of WTA costs varies between Rp100,000.00 until IDR 1.300.000,00 The Sperman correlation test shows that there is a significant correlation between income and expenditure, between willingness to accept WTA value and WTA value and between expenditure and willingness to accept WTA value. Correlation is low and different directional, except the correlation between income and expenditure is in the same directionKata kunci : Sungai Baturusa, PenambanganTimah, Kualitas Air, IndeksPencemaran.